The genome evolution and low-phosphorus adaptation in white lupin - Weifeng Xu (Nature Portfolio, 2020)
White lupin is a legume crop that develops cluster roots for efficient phosphate acquisition. Here, the authors assemble its triplicated genome, reveal gene expression difference among sub-genomes, and characterize possible pathways related to high phosphorus-use efficiency.